SECOND LANGUAGE ACQUISITION IN CHILDREN WITH BATAK TOBA AS THEIR FIRST LANGUAGE: CHALLENGES AND DEVELOPMENT PATTERNS - Hutabarat, Esra Delima; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2024)
This study examines second language acquisition (SLA) in children with Toba Batak as their first language, focusing on challenges in phonology, syntax, and vocabulary. Pronouncing phonemes that are lacking in Toba Batak, including /f/ and /v/, and translating Toba Batak grammatical patterns to English or Indonesian are two major linguistic challenges. SLA development is greatly impacted by social and cultural elements, such as a strong attachment to the Toba Batak identity and little exposure to second-language contexts. The study emphasizes the value of striking a balance between language instruction and cultural preservation while highlighting the significance that early exposure and a multilingual setting have in promoting SLA. Longitudinal research and improved language regulations are among the suggestions made to encourage bilingualism without undermining cultural identity. Keyword: Second Language Acquisition, Toba Batak, Phonology, Syntax, Social culture